Estimation of Surveillance Radar Location Based on TDOA Using a Single UAV - Lee, Hangyeol; Park, Jongho; Lim, Jaesung (Journal of Korean Institute of Communications and Information Sciences, 2021)
In this paper, an estimation of radar location using a single rotating UAV(Unmanned Aerial Vehicle) is proposed. With a steady level coordinated turn, the UAV captures signals from enemy radars and sends TOA(Time of Arrival) measurements and locations to a ground control station. It calculates TDOA(Time Difference of Arrival) and estimates the location of the target based on LSM(Least Square Method) and EKF(Extended Kalman Filter). Then, the UAV computes the center of the coordinated turn and flies to the corresponding position. In the numerical simulation, accuracy around 1% is shown in the case where the minimum distance between the UAV and the target is 40km. Also, as the turning radius of the UAV gets larger, the probability of having a large error decreases. Therefore, it is expected that an accurate long-range location estimation is possible at a low cost. Also, the proposed algorithm can be improved by applying other estimation algorithms, or by additionally utilizing FDOA(Frequency Difference of Arrival), and AOA(Angle of Arrival) values.
Keywords: Surveillance Radar; TDOA; UAV